(untitled) (Fiep Bulletin - online, 2014)
This article aims to map the transition from kindergarten to first year giving special emphasis on the physical space of classrooms. The methodology is inspired by the case study provided multiple sources of evidence. From these indicators, we can see that the space of kindergarten is a welcoming environment in which playfulness is a dimension of language, because the child is expressed with freedom, imagination, creativity and delight through drawing, dance and jokes. In the first year, the expression occurs, most often, by use of the written word, and the few times that the play is associated. With the advance of passage for the coming years, features such as spontaneity, creativity, imagination, pleasure, joy and fun, and the size of the body, movement and physical activities tend to be lost, leading to schedules filled with school contents to be developed in a short period of time varying between 45 minutes and 1h30min, in which the teacher, often without any dialogue knowledge, various works content.